Ledhug: Syncretic Music Culture in Magetan - Dea Lunny Primamona; Dolly Nofer (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2019)
In Magetan, East Java, Indonesia, the turn of the Javanese and Islamic years is marked by the celebration of Ledhug Sura. The celebration consisted of various events such as the Ledhug music festival, the people's market, the carnival, the night of repentance and the climax at the Andum Berkah Bolu Rahayu procession. This is a carnival for cakes and agricultural products which are considered to bring blessings to the community. This research focuses on the ledhug (lesung and bedhug, which means a combination of mortar and drum) music festival. Mortar and bedhug are the main focus of this article. The purpose of this study is to (1) reveal the form of the conception of ledhug music and (2) recognize the concepts contained in the ledhug music. Data mining methods include fieldwork using observation and interview techniques; literature review; and data presentation methods using descriptive-interpretative techniques. Based on the results of fieldwork and reading or interpretation of the ledhug music culture, it was concluded that the ledhug music performance was the result of a process of cultural syncretism. Ledhug music culture exists as a blend of musical elements from Javanese and Islamic music culture. Cultural syncretism in the context of ledhug is a deliberately produced discourse building, namely as a form of resolution of the reality of cultural contestation between the two ideologies that existed in Magetan.